Adubação com KCl revestido na cultura do milho no Cerrado - Rodrigues, Mateus A. de C. [UNESP]; Buzetti, Salatiér [UNESP]; Teixeira Filho, Marcelo C. M. [UNESP]; Garcia, Cássia M. P. [UNESP]; Andreotti, Marcelo [UNESP] (Univ Fed Paraiba Ccsa, 2014)
The use of coated potassium chloride can provide greater absorption of potassium resulting in the alteration of leaf contents, production components and grain yield. The objective of this study was to evaluate the effect of potassium doses using potassium chloride conventional or coated by polymer, in the corn crop under conditions of brazilian Savanna with low altitude. The experiment was conducted in Selviria, MS, Brazil, in a clayey Oxisol. The treatments consisted of four doses of K2O (0, 40, 80 and 120 kg ha(-1)), applied at sowing, and two sources: potassium chloride and potassium chloride coated by polymers. A randomized block design with eight treatments and four replications was used. The coated KCl is not efficient under the soil and climatic conditions studied, because it provided results similar to the conventional KCl for the K foliar content, crop components and grain yield of irrigated corn. The increment of K2O doses influenced positively the K and chlorophyll leaf contents, plant and spike insertion height and the number of rows and grains per spike. The maximum mean yield obtained was with 83.5 kg ha(-1) of K2O.
Fertilization with coated KCl in corn in the Savannah
Keywords: Crop Components; Grain yield; Potassium fertilization; Slow release fertilizer; Zea mays